Smart Characterization—An Integrated Approach for Evaluating a Complex 1, 4‐Dioxane Site. Issue 1 (5th December 2016) - Curry, Patrick; Welty, Nicklaus; Wright, Jesse; Favero, Dave; Quinnan, Joseph
Abstract : Smart characterization approaches apply the latest high‐resolution site characterization methods to find the contaminant mass flux, by integrating relative permeability mapping, classical hydrostratigraphy interpretation, and high‐density groundwater and saturated soil sampling. The key factor that makes Smart characterization different is the application of quantitative saturated soil sampling in less permeable slow advection and storage zones to diagnose plume maturity and understand its implications for remedy selection and performance. Because direct sensing tools like the membrane interface probe are capable of providing screening‐level assessments for hydrocarbons and chlorinated solvents in storage zones, but not 1, 4‐dioxane, the recommended Smart approach involves application of specialized high‐capacity mobile laboratories or rapid turn‐around using fixed commercial labs. In addition to the benefit of rapidly characterizing sites, Smart characterization facilitates a flux‐based conceptual site model, which allows stakeholders to focus remedies on the mobile portion of the contaminant mass or, in effect, the mass that matters. Through systematic planning and implementation, predesign characterization can be completed to optimize source and plume remedy strategies, balancing investment in Smart characterization with reductions in total life‐cycle costs to ensure that an appropriate return on investigation is obtained. © 2016 Wiley Periodicals, Inc.